2017
DOI: 10.1149/2.0881704jes
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability of Nanostructured Thin Film Electrodes at Operating Potentials

Abstract: Long-term stability of nanostructured thin film (NSTF) catalysts at operating potentials has been investigated. Compared to high surface area Pt/C catalysts, NSTF electrodes show 20-50x smaller F − emission rates (FER) because of their high specific activity for oxygen reduction reaction (ORR), but are susceptible to poisoning by the products of membrane degradation because of their low electrochemically active surface area (ECSA). The observed voltage degradation rates at potentials corresponding to 1-1.5 A/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This could be attributed to ongoing morphological changes and loss of 111‐facets as well as the leaching of Ni and Mo [7,23] . Additionally during cycling, impurities can accumulate on the electrode and result in lower observed SA [38] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be attributed to ongoing morphological changes and loss of 111‐facets as well as the leaching of Ni and Mo [7,23] . Additionally during cycling, impurities can accumulate on the electrode and result in lower observed SA [38] …”
Section: Resultsmentioning
confidence: 99%
“…[7,23] Additionally during cycling, impurities can accumulate on the electrode and result in lower observed SA. [38] Figure 3c gives insights into the reproducibility. While the initial SA development show higher deviations (6-15 %) up to the 9th ORR-cycle, a continuous cycling leads to a converge of the average SA result.…”
Section: Cycling Either In N 2 or O 2 Saturated Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…A typical 50-cm 2 electrode area, quad-serpentine test cell obtained from Fuel Cell Technologies was used for the cell testing. All MEAs were first conditioned using a process referred to as ''thermal cycling'' and as described in Ahluwalia et al 47 See Supplemental Experimental Procedures for further details on cells and materials.…”
Section: Experimental Procedures Materials Fabrication and Assemblymentioning
confidence: 99%
“…Qi et al varied the wt% of Pt/C and found that 20% Pt/C and 30% Nafion is best combination in case of the E‐TEK catalyst material. Other groups optimized performance of low loaded MEAs by using ionomer‐free NSTF (nanostructured thin films) to reduce the oxygen transport resistance , . Others have studied catalyst layer preparation techniques or have used stable carbon composite catalysts for catalyst layer preparation .…”
Section: Introductionmentioning
confidence: 99%